(untitled) (Indian Journal of Chemical Technology (IJCT), 2025)
Lubricating oils are essential in the mechanical industry, but their petroleum-based origin raises increasing environmental concerns. Bio-based lubricants offer a potential solution, provided they can achieve comparable performance and cost-competitiveness with conventional mineral-based and synthetic lubricants. Therefore, this study investigated the performance, biodegradability, and toxicity of pyrolysis-derived algal oil as a sustainable and environmentally friendly alternative to traditional lubricating oils. The pyrolytic algal-based lubricating oil exhibited a flash point of 273°C, indicating a reduced fire hazard, and a pour point of -15°C, suggesting suitability for low-temperature applications. The key advantages of this algal lubricating oil are its high biodegradability and low toxicity. It also demonstrated 85% degradation within 28 days. Toxicity levels have been assessed using both aquatic organisms and soil microbes. This algal lubricating oil is found to have low toxicity, with LC50 values of 125 mg/L for Daphnia magna and 150 mg/L for Danio rerio. Furthermore, the results showed that this algal lubricating oil enhanced soil microbial activity by 10%. The impact on plant life was assessed by monitoring germination and growth. A 90% germination rate is recorded, and subsequent plant growth is positive, with an observed biomass increase of up to 85%. Spill recovery tests demonstrated high recovery efficiencies of 85% in water and 80% in soil. The findings of this study support the use of pyrolysis-derived algal oil as a sustainable alternative to traditional lubricants.